Biobibliometric portrait of B.K Sen: A librarian, information scientist and scientometrician - Dutta, Bidyarthi (Malaysian Journal of Library and Information Science, 2019)
This biobibliometric study highlights the major aspects of the career of the Indian librarian and information scientist, Bimal Kanti Sen. As a professional librarian, he took major initiatives toenhance practical scientometric programs in India. He has contributed 390 writings since 1964 to 2018, i.e. over 55 years,including his service and retirement period. He authored seven writings per year on an average. Of the 390 writings, 184 are research articles, which means he contributed about three papers per year consistently over hisentire career period. Other than research articles, his contributions include technical and popular articles (55, 14%), writings on terminology (48, 13%), course materials (37, 10%), books (12, 3%), letters (12, 3%), book reviews (9, 2.5%), catalogue (9, 2.5%), review articles (5, 1.3%), reports (5, 1.3%) and bibliographies (4, 1%). The year-wise distribution of authorship pattern, collaborative authors and degree of collaboration, author productivity, core journals and highly cited publications are identified in this paper. Different academic indicators of Bimal Kanti Sen are calculated on the basis of citation data available from Web of Science, Scopus and Google Scholar. His academic and research activitiessteadily increased with his age. His most notable research work was normalization of the Impact Factor and identifying Impact Factor of non-SCI journal. His other notable works include biobibliometric analysis, history of science, lexicography, etc. He is still academically active and continues to add to the knowledge repository.